Determination of the effectiveness of carbons obtained from the co-carbonization of duckweed and waste coffee on crystal violet removal - Olam, Mikail (My University, 2023)
With the development of industry, the rate of industrial dyes in municipal wastewater is increasing day by day. The use of environmentally friendly, economical and highly efficient adsorbents for their removal has recently gained importance. In this study, crystal violet (CV) in wastewater was removed by carbonizing waste coffee (wC) and duckweed (DW) formed on the surface of municipal wastewater treatment plant pools. DW and wC samples were carbonized together and separately at N2 of 100 mL/min and 800 °C in a tubular reactor for 90 minutes. Adsorption experimental studies were performed at adsorbent amount of 0.5 g, 6 pH, temperature of 30 °C, initial concentration of 50-100 mg/L and contact time of 60 min. SEM and FTIR analyzes were performed for the characterization of the adsorbents. In XRD analysis, wC and carbonized wC (cwC) were amorphous, and co-carbonized wC and DW (cDW/wC) was semi-crystalline. The most effective adsorbent for CV dye removal from wastewater is DW/wC. Its adsorption capacity was 8.29 mg/L, and its CV removal was 83%.
Keywords: Adsorption; carbonization; crystal violet; duckweed; waste coffee